Intention to Receive COVID-19 Vaccine by U.S. Health Sciences University Employees - Travis S. Dowdle; Jeff Dennis; Kenneth M. Nugent; Theresa Byrd (SAGE Publishing, 2021)
Objectives: Understanding vaccine intentions and attitudes of health professionals is critical as the Pfizer-BioNTech and the Moderna COVID19 vaccines are being administered throughout the United States. This study estimates the level of vaccine hesitancy at a health sciences center in West Texas prior to the distribution of the vaccines. Methods: An analytical cross-sectional study was performed via anonymous Qualtrics survey administered to approximately 4500 faculty, staff, postdoctoral research associates/medical residents, and employees at a multi-campus health sciences university in the United States. Respondents were asked demographic questions and intention to receive the vaccine. Factors associated with the intention to receive a vaccine were determined using logistic regression analysis. Results: A total sample of 2258 subjects were evaluated (50.0% response rate). Among all respondents, 64.6% reported that they would probably or definitely receive the COVID-19 vaccine. Men had higher levels of intention to receive the vaccine (OR = 2.11, 95% CI 1.64-2.71); respondents who indicated yearly influenza vaccines are necessary were also more likely to receive the vaccine (OR = 6.04, 95% CI 4.70-7.75). Eighty-three percent of faculty and 56% of the staff reported intention to receive the vaccine. Respondents who had previously tested positive for COVID-19 reported more interest in receiving the vaccine (58.5% yes vs 41.5% no). Conclusion: In this study, the intention to receive the COVID-19 vaccination at a United States health sciences center falls below the necessary herd immunity estimates. Public health initiatives must be developed to decrease vaccine hesitancy, especially among health professionals.